2019
DOI: 10.1186/s12936-019-2842-7
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of divergent anti-malarial treatment responses in peripheral blood from adults and young children in Malawi

Abstract: Background Heterogeneity in the immune response to parasite infection is mediated in part by differences in host genetics, gender, and age group. In infants and young children, ongoing immunological maturation often results in increased susceptibility to infection and variable responses to drug treatment, increasing the risk of complications. Even though significant age-associated effects on host cytokine responses to Plasmodium falciparum infection have been identified,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…In children and adults with malaria, elevated plasma levels of nitrites and nitrates have been associated with more rapid parasite clearance [139]. Indeed, previous studies have shown that children infected with P. falciparum had elevated levels of NO and iNOS activity, suggesting the protective role of NO in children with malaria [140].…”
Section: Nitric Oxide In Malariamentioning
confidence: 99%
“…In children and adults with malaria, elevated plasma levels of nitrites and nitrates have been associated with more rapid parasite clearance [139]. Indeed, previous studies have shown that children infected with P. falciparum had elevated levels of NO and iNOS activity, suggesting the protective role of NO in children with malaria [140].…”
Section: Nitric Oxide In Malariamentioning
confidence: 99%